2014
DOI: 10.1186/1743-422x-11-70
|View full text |Cite
|
Sign up to set email alerts
|

Hyperimmune intravenous immunoglobulin containing high titers of pandemic H1N1 hemagglutinin and neuraminidase antibodies provides dose-dependent protection against lethal virus challenge in SCID mice

Abstract: BackgroundConvalescent plasma and fractionated immunoglobulins have been suggested as prophylactic or therapeutic interventions during an influenza pandemic.FindingsIntravenous immunoglobulin (IVIG) preparations manufactured from human plasma collected before the 2009 H1N1 influenza pandemic, and post-pandemic hyperimmune (H)-IVIG preparations were characterized with respect to hemagglutination inhibition (HI), microneutralization (MN) and neuraminidase-inhibiting (NAi) antibody titers against pandemic H1N1 (p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 21 publications
0
20
0
Order By: Relevance
“…To speed production, individual plasma donations were pooled based on self‐reported history and not tested for the presence of neutralizing influenza antibodies prior to FLUIGIV production. The resulting product had high anti‐pdmH1N1 antibody levels and protected immune‐deficient mice from lethal disease . Protection against lethal challenge with the mouse‐adapted pandemic strain A/California/04/09 in a preexposure prophylaxis study was also observed in immunocompetent BALB/c mice (A. M. Khalenkov and D. Scott, unpublished data, 2017).…”
Section: Discussionmentioning
confidence: 90%
“…To speed production, individual plasma donations were pooled based on self‐reported history and not tested for the presence of neutralizing influenza antibodies prior to FLUIGIV production. The resulting product had high anti‐pdmH1N1 antibody levels and protected immune‐deficient mice from lethal disease . Protection against lethal challenge with the mouse‐adapted pandemic strain A/California/04/09 in a preexposure prophylaxis study was also observed in immunocompetent BALB/c mice (A. M. Khalenkov and D. Scott, unpublished data, 2017).…”
Section: Discussionmentioning
confidence: 90%
“…Thus these pigs provide an additional model to study the immune response mechanisms involved in the protection and/or resolution of IAV infection, particularly in regards to the adaptive compartment of the immune system. Because swine are natural hosts for IAV, are genetically and anatomically similar to humans [36], and also have an immune genome component that is very similar to humans [37], these SCID pigs represent an improved model to the use of SCID mice to evaluate potential therapies and preventive strategies for human influenza [38]. …”
Section: Discussionmentioning
confidence: 99%
“…One potential therapeutic option is passive immunotherapy with convalescent plasma or hyperimmune intravenous immunoglobulin (H-IVIG) (12). Previous work has suggested that this approach might be an effective treatment for infections with Spanish InfA (H1N1), avian InfA (H5N1), 2009 pandemic InfA (H1N1), SARS coronavirus (SARS-CoV), and Middle East respiratory syndrome coronavirus (MERS-CoV), among others (12)(13)(14)(15)(16)(17)(18). However, few studies have been reported using this approach for the most prevalent viral pathogens.…”
Section: Introductionmentioning
confidence: 99%